Comparative Efficacy and Acceptability of Nonpharmacotherapy in the Treatment of Inattention for ADHD: A Network Meta-Analysis - Xusheng Che; Choi Jong-Hwan; Xiuhai Shang (Complexity)
This article is aimed to compare the efficacy and acceptability of exercise intervention with other nonpharmacological therapies in improving attention in ADHD patients and then rank those therapies. Methods. Relevant RCT studies from the Cochrane Library, Web of Science, Psycinfo, and PubMed were systematically searched from January 2011 to January 2020. The literature was screened, and the researchers extracted and used Stata16 and WinBugs1.4 independently to analyze the data. Results. The improvement of “attention deficit” in ADHD patients was measured in 83 independent studies with 4,998 participants and 14 nonpharmacological therapies. Therapies were ranked as follows, according to the efficacy and acceptability of the cumulative probability area under the curve (SUCRA): (1) meditation and cognitive; (2) sport intervention therapy; (3) vitamin and mineral; (4) cognitive behavioral therapy; (5) computer training; (6) psychological education; (7) working memory training; (8) neurofeedback therapy; (9) polyunsaturated fatty acids; (10) mineral supplements; (11) meditation; (12) vitamin; (13) biofeedback therapy; and (14) school-based training. However, because the effect size of meditation and cognitive therapy was at a marginally significant level (SMD = −1.07, (−2.15, 0.00)), the robustness of the results was far lower than that of sport intervention therapy. Therefore, careful interpretation is needed in practice. Conclusion. Considering the efficacy and acceptability of various nonpharmacological therapies, sport intervention has a more stable effect on the improvement of attention deficit. Secondly, meditation and cognitive therapy, cognitive behavioral therapy, and computer training can also be effective complementary tools.